A study to determine a suitable statutory liability regime for carriage of goods by road in Malaysia / Norziela Mohamed Nasir ... [et al.] - Mohamed Nasir, Norziela; Noor Azman, Nor Assalinah; Khairudin, Nur Alya Syahirah; Mohd Fadzil, Nur Farahna Fateen (2013)
This research proposal will focus on the study of the need for a regime concerning on the carriage of goods by road in Malaysia in reference with the Convention on the Contract of International Carriage of Goods by Road (CMR). We will be touching on the current situation in Malaysia, in which the carriage of goods by road in Malaysia is not governed by any specific regime. We will also include the problems occurred in Malaysia that call for the need of such new regime. Furthermore, we will analyse in depth on CMR especially the matters concerning liability and see how effective the application of the Convention in foreign countries. However, in order to cany out this project paper, there are several difficulties that might arise in carrying out the research and the solutions are discussed. The achievement in this research paper is that we have suggested the ratification of the CMR is not necessary and the Malaysian legal system should adopt only certain Articles of the Convention that are deemed to be necessary to make Malaysian law better.